ANALISA PENGENDALIAN KUALITAS PRODUK COVER MOTOR PADA PT. ABC MENGGUNAKAN METODE BORDA DAN KAIZEN - Elly Wuryaningtyas Yunitasari; Emmy Nurhayati (Universitas Sarjanawiyata Tamansiswa, 2016)
This research generally aims to describe the effects of civic learning in nurturing students’ political literacy, and specifically aims to examine and discover the effects of civic components application that consist of civic learning and competences on the level of students’ political literacy. This research used quantitative approach and descriptive method of survey technique. From the research results, it could be generally concluded that: (1) civic learning through various democratic learning methods strengthened the effects of civic education in nurturing students’ political literacy, (2) the better quality of students’ civic competences the higher their level of political literacy, and (3) an effective and meaningful civic competences could directly improve students’ political literacy